Chapter I Doria e la chiesa di San Matteo a Genova nella seconda metà del Duecento - Guglielmotti, Paola (Reti Medievali E-Book, 2021)
The essay addresses the problem of the relationship between large aristocratic families and "noble parishes" in Genoa, by considering the case of the Doria and the church of San Matteo, founded in 1125 and whose reconstruction was planned in 1278. On the one hand, three qualifying aspects of the Doria kinship are examined in order to understand the role of the small church in enhancing the coordination of the group: i.e., positions of leadership and command in the maritime city and in its government; dispersion and presence outside Genoa; numerical strength, residence and leadership. On the other hand, the article considers the insertion of San Matteo in the monastic network (not only in Liguria) headed by the abbey of San Fruttuoso, and how its reconstruction allowed for the diversification of the large family internal and external relevance. The conclusion, thanks to the comparison with the experiences of other important urban families, shows the uniqueness of this case study and how broader and more systematic comparisons should be made, even outside the Genoese context.